2003
DOI: 10.1073/pnas.1635112100
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic proteins require plasma fibronectin or vitronectin for in vivo activity

Abstract: Fragmentation of various extracellular matrix and blood proteins generates antiangiogenic substances that are physiological regulators of angiogenesis. Some of these compounds are in clinical trials as inhibitors of tumor angiogenesis. Anastellin, an antiangiogenic protein fragment derived from fibronectin, was unable to inhibit matrigel plug angiogenesis in mice that lack plasma fibronectin. Anastellin was fully active in mice that are null for vitronectin, which, like fibronectin, is a major adhesion protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(78 citation statements)
references
References 35 publications
4
74
0
Order By: Relevance
“…Specific RGD motifs have been identified as potential binding partners for ES and similar antiangiogenic proteins. 35 Experiments performed in order to test effects of ES delivered by Alzet pumps on endothelial permeability in vivo showed inhibition of VEGF-induced permeability only after 3 days of treatment (unpublished data), supporting that ES has to saturate all binding targets before a systemic effect can be observed. Since systemic concentration of ES reached by microbeads is only slightly elevated over normal levels, we speculate that selective accumulation in sensitive endothelia achieved by continuous delivery might be sufficient for the effect observed.…”
Section: Spotlightmentioning
confidence: 87%
“…Specific RGD motifs have been identified as potential binding partners for ES and similar antiangiogenic proteins. 35 Experiments performed in order to test effects of ES delivered by Alzet pumps on endothelial permeability in vivo showed inhibition of VEGF-induced permeability only after 3 days of treatment (unpublished data), supporting that ES has to saturate all binding targets before a systemic effect can be observed. Since systemic concentration of ES reached by microbeads is only slightly elevated over normal levels, we speculate that selective accumulation in sensitive endothelia achieved by continuous delivery might be sufficient for the effect observed.…”
Section: Spotlightmentioning
confidence: 87%
“…Interestingly, the activity of endostatin is impaired in both fibronectindeficient and vitronectin-deficient mice. This suggests a shared mechanism of action for antiangiogenic factors derived from ECM and plasma proteins (66).…”
Section: Matrix-derived Inhibitors Of Angiogenesismentioning
confidence: 93%
“…Subsequent studies of anastellin have revealed potentially important biological activities when injected peritoneally into mice, including inhibition of angiogenesis and tumor growth (17). These activities required plasma FN (18), so it is likely that sFN plays a role. When tested in cell culture, Bourdoulous et al (19) found that high concentrations of anastellin (20 M) blocked FN matrix formation and caused an established matrix to disappear after 16 h of treatment.…”
Section: Fibronectin (Fn)mentioning
confidence: 99%